Conservation status of the Oyster Reef Ecosystem of Southern and Eastern Australia - Chris L. Gillies; Sarah A. Castine; Heidi K. Alleway; Christine Crawford; James A. Fitzsimons; Boze Hancock; Paul Koch; Dominic McAfee; Ian M. McLeod; Philine S.E. zu Ermgassen (Global Ecology and Conservation, 2020)
Reef ecosystems all over the world are in decline and managers urgently need information that can assess management interventions and set national conservation targets. We assess the conservation status and risk of ecosystem collapse for the Oyster Reef Ecosystem of Southern and Eastern Australia, which comprises two community sub-types established by Saccostrea glomerata (Sydney rock oyster) and Ostrea angasi (Australian flat oyster), consistent with the IUCN Red List of Ecosystems risk assessment process. We established: (i) key aspects of the ecosystem including: ecological description, biological characteristics, condition and collapse thresholds, natural and threatening processes; (ii) previous and current extent of occurrence and current area of occupancy; and (iii) its likelihood of collapse within the next 50–100 years. The most severe risk rating occurred for Criterion A: Reduction in Extent (since 1750) and Criterion D: Disruption of biotic processes (since 1750), although assessment varied from Least Concern to Critically Endangered amongst the four criteria assessed. Our overall assessment ranks the risk of collapse for the ecosystem (including both community sub-types) as Critically Endangered with a high degree of confidence. Our results suggest the need for rapid intervention to protect remaining reefs and undertake restoration at suitable sites. Several restoration projects have already demonstrated this is feasible, and Australia is well equipped with government policies and regulatory mechanisms to support the future conservation and recovery of temperate oyster ecosystems.